Multi-site musculoskeletal pain in adolescence: occurrence, determinants, and consequences - Paananen, M. (Markus) (Oulun yliopisto, 2011)
Abstract Recent studies in adults have shown that musculoskeletal (MS) pains are often experienced at several body sites. The number of pain sites has been shown to be proportional to poor health outcomes, such as functional ability and health-related quality of life (HRQoL). This study investigated the occurrence and persistence of MS pain in multiple locations, determinants of multiple-site pain, and the impact of multiple-site pain on HRQoL and health care use among adolescents aged 16 to 19. The data were based on three inquiries that were administered to the adolescents of the Northern Finland Birth Cohort 1986. MS pain was common and often occurred at multiple sites. Moreover, the majority of adolescents with multiple-site pain at 16 reported multiple-site pain also at 18. Multiple-site MS pains were strongly associated with psychosocial complaints, but also with high physical activity level, long sitting time, short sleeping time, smoking, and overweight. Emotional problems, behavioral problems, and high sitting time among males, and emotional problems, high physical activity level, short sleeping time, and smoking among females were predictive factors for the persistence of multiple-site pain. The likelihood of reduced HRQoL increased according to the number of MS pain sites. A trend toward an increase in health care use with the number of pain sites was also observed. Reporting pain in multiple sites in adolescence may have both peripheral (tissue origin) and central (pain experience) causes. As multiple-site pain in adolescence may predict subsequent MS morbidity, the adolescents who are at highest risk and also at the highest need of health promotion should be identified in further studies. Tiivistelmä Aikuisväestössä tehtyjen tutkimusten perusteella tuki- ja liikuntaelimistön kivut esiintyvät tavallisesti usealla kehon alueella samanaikaisesti. Monikipuisuudella näyttää olevan epäedullisia vaikutuksia useisiin terveyteen liittyviin ilmiöihin kuten toiminta- ja työkykyyn sekä elämänlaatuun. Tässä ...